Projeto Casulo: uma experiência de educação sexual no ensino fundamental Cocoon Project : an experience with sexual education in elementary school - Castello Branco Rena, Luiz Carlos (Revista Linhas, 2007)
Relato de uma experiência de educação sexual na 4ª série do Ensino Fundamental de uma escola privada de Belo Horizonte. Apresentamos as condições de implantação do programa, defendemos uma concepção de educação sexual, discutindo a pertinência da intervenção pedagógica no campo da sexualidade com grupos de adolescentes e compartilhamos uma experiência de sala de aula avaliando o impacto da ação educativa sobre os agentes envolvidos. PALAVRAS-CHAVE: Adolescência. Sexualidade. Educação ABSTRACT: This paper presents an experience with sexual education in the fourth grade of a private elementary school in Belo Horizonte, Brazil and the conditions under which it was implemented. We defend a concept of sexual education and discuss the relevance of pedagogic intervention in the field of sexuality with adolescent groups. We also share a classroom experience to evaluate the impact of educational action on the agents involved. KEY WORDS: Adolescence. Sexuality. Education